DEVELOPING A MODEL OF COGNITIVE PSYCHOTHERAPY BASED ON INDONESIA ISLAMIC’ VALUES ON TERRORIST - Arman Marwing (Islam Realitas: Journal of Islamic and Social Studies, 2018)
High rate of recidivism on terrorists  indicates  the weakness of deradicalization programs. This study aims to offer  a solution through development of a cognitive psychotherapy  which based on  Indonesia Islam values. The integration among Islam, culture and psychotherapy is able to help the terrorists to identify and restructure their cognitive that causes their emotion and destructive  behaviors. This qualitivative study mixes between literature and phenomenology approaches. This study found that there are conflicting differences between the views of the terrorists and ijtihad of Indonesia Ulama regarding  khilafah, jihad and takfiri concepts. In Addition, the model of cognitive psychotherapy based on Indonesian Islamic values was developed by content analysis and its implementation followed several systematic procedures such as anamnesis, assessment, diagnosis, intervention, result of intervention,  follow up. Embracing humantic approach and collaborative Empiricism procesures enable the therapy effectively internalize Indonesia Islamic values such as Tasamuh (tolerance), Tawasuth (moderate), Tawazun (balanced), 'Adalah (Justice) and Ukhuwah (Brotherhood), which includes ukhuwah Islamiyah (other Muslims), Ukhuwah Wathoniyah (fellow citizens), Ukhuwah basyariah (fellow citizens) for the terrorists. These values could be intentionally internalized by terrorist itself and threfore it would be effective model  to modify terrorists’ destructive thought schemas (cognitive), emotion and behavior to be adaptive.      Abstrak Residivisme pelaku terorisme yang tinggi menunjukkan kelemahan program deradikalisasi. Penelitian ini  bertujuan untuk menawarkan konstruksi model psikoterapi kognitif berbasis nilai Islam Indonesia sebagai salah satu solusi. Sebuah integrasi antara Islam, budaya dan psikoterapi dalam membantu pelaku terorisme mengidentifikasi dan merestrukturisasi kognitif yang menjadi penyebab emosi dan perilaku destruktif. Metode yang digunakan adalah penelitian kualitatif dengan menggunakan perpaduan studi literatur dan fenomenologi. Hasil penelitian menemukan adanya perbedaan pandangan  yang kontradiktif antara pelaku terorisme dan ijtihad Ulama Nusantara mengenai konsep khilafah, Jihad dan Takfiri.  Selain itu model psikoterapi kognitif berbasis nilai Islam Indonesia dihasilkan melalui pengujian  isi serta menerapkan beberapa prosedur atau tahapan yang sistematis yaitu anamnesis, pemeriksaan, diagnosis, kontruksi model terapi, hasil intervensi dan tindak lanjut. Melalui pendekatan humanis dan prosedur collaborative Empiricism terapi ini memungkinkan nilai-nilai Islam Indonesia yang mengedepankan Tasamuh (toleransi), Tawasuth (moderat), Tawazun (berimbang),‘ Adalah  (Keadilan), dan Ukhuwah (Persaudaraan) yang meliputi ukhuwah Islamiyah (sesama Islam), Ukhuwah Wathoniyah (Sesama warga negara), Ukhuwah basyariah (sesama umat manusia) dapat terinternalisasi dengan kesadaran dan tanggung jawab dari pelaku teroris itu sendiri, serta dapat efektif mengubah skema berpikir,emosi dan perilaku teroris menjadi adaptif.